HINARI Usage Patterns and Trends in Nigerian Universities in Five Years (2010-2014) (2016)
The digital divide is a global challenge. The Health Internetwork Access to Research Initiative (HINARI) is one of the most successful efforts aimed at bridging the digital divide in access to health information in developing countries. Despite the availability of this resource free of charge to not-for-profit institutions in developing countries, few studies are available that investigate its usage patterns and trend in Nigeria. Data for the study were obtained from HINARI server located in the WHO Library in Geneva. The data were the yearly log and statistics of usage of HINARI in universities in Nigeria from 2010 to 2014. The collected log data was analyzed using Microsoft Excel. Descriptive statistics including frequency counts, percentages and bar charts were used. More (68.0%) public than private (32.0%) universities in Nigeria are registered with HINARI. Of the registered institutions, (37.0%) are located in the South-West zone. A total of 201,110 user’s accessed HINARI resources in universities in the six zones across the country during the five-year period. While universities in the South-West zone recorded the highest (63.4%) users, those in the North-East had the lowest (3.1%). The highest (97,229) number of HINARI users in Nigerian universities was recorded in 2012 while the lowest figure occurred in 2014. This study shows that HINARI was used in universities in all five geo-political zones in Nigeria however, usage trends revealed a sharp decline in 2014. Further studies are recommended to determine alternative sources used by students, researchers and healthcare providers to meet their information needs.